Comparative Analysis of Combustion of Qualified Composite Fuel for the Transitional Period in the Household and Communal Sector in Poland - Bembenek Michał; Dzik Tomasz; Smyła Jarosław; Kozłowski Artur; Wojtas Piotr (Management Systems in Production Engineering, 2022)
The article presents the results of laboratory combustion tests of the microbriquette obtained from useless coal (grain class of < 5 mm) generated in the production of “eco-pea” (eko-groszek) coal. The briquettes of 1.5 and 2.5 cm3 were made in a roller press of crushed coal granulation down to 2 mm, mixed with a binder and/or catalytic additives and sorbents, then dried to final moisture of about 7%. The tests were carried out on a specially designed stand enabling to determine the differential curve of the weight loss of samples heated to the ignition temperature and then burnt with laminar airflow by natural chimney draft. Comparative tests were carried out with ecopea coal from the “ZG Sobieski” mine. The results indicate that composite fuels, in the form of microbriquette, ignite faster, burn at a higher temperature and leave less ash when burned than lump coal. The greater reactivity of the briquette concerning the lump coal allows for minimizing the air rate by about 10%, which also reduces the exhaust gas volume by the same amount and the stack losses. It reduces the velocity of dust lifting, which leads to the reduction of their emission.